2021
DOI: 10.3389/fmars.2021.653447
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of the Nuclear Receptor Gene Family in Macrostomum lignano Imply Its Evolutionary Diversification

Abstract: Nuclear receptors (NRs), a series of key transcription factors that are mostly activated by endogenous ligands or environmental xenobiotics, are reportedly good phylogenetic markers of animal genome evolution. As the early diverging class of bilaterians, however, a comprehensive view of the NR family in a marine free-living flatworm Macrostomum lignano and comparative information in flatworms are still lacking, which is of significance to address the evolutionary diversification of the NR family and imply the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Our previous study showed that two 2DBD-NRs were present in Rhabditophora Macrostomum lignano [ 16 , 21 ] and four in Schmidtea mediterranea . Three members were present in parasitic species from Platyhelminths including Class Monogenea, Cestoda and Trematoda, respectively [ 12 , 14 , 15 , 17 21 ].…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Our previous study showed that two 2DBD-NRs were present in Rhabditophora Macrostomum lignano [ 16 , 21 ] and four in Schmidtea mediterranea . Three members were present in parasitic species from Platyhelminths including Class Monogenea, Cestoda and Trematoda, respectively [ 12 , 14 , 15 , 17 21 ].…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Previously, we suggested placing 2DBD-NRs in a new NR subfamily (NR subfamily 7, NR7) when we discovered the 2DBD-NRs [6,8] and this was accepted by some other studies [10,44,45]. However, NR7 was recently used to describe NRs [46] previously known as NR8 members [45] and amphioxus NR1Hs [27,47].…”
Section: ) Nr Subfamilies Are Designated By Arabic Numerals (Nr7 2dbd...mentioning
confidence: 99%
“…Phylogenetic analysis of DBD sequences showed that all of these 2DBD-NRs belonged to a monophyletic group and suggested that 2DBD-NRs originated from a common ancestor gene [8]. Recently, 2DBD-NRs were only identified and/or isolated in Platyhelminths [6,[8][9][10][11][12][13][14][15] and in Mollusca [16,17]. Until now, there are very few studies on 2DBD-NRs.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, it has not been possible to identify subfamily 3 NRs in Platyhelminthes [21,72], so this class of proteins seems to have been lost in this phylum. However, recent genome sequence analysis studies identified several ERRs (estrogen-related receptor) belonging to subfamily 3 [37,49].…”
Section: Subfamilymentioning
confidence: 99%
“…This new group has not yet been included in the classification system described by the NR Nomenclature Committee [21,34]. However, recent publications already classify it as a subfamily NR7 [37]. Furthermore, nuclear receptors can be classified according to their mechanism of action into four types (I-IV).…”
Section: Introductionmentioning
confidence: 99%